Brief mock-scan training reduces head motion during real scanning for children: A growth curve study - Peng Gao; Yin-Shan Wang; Qiu-Yu Lu; Meng-Jie Rong; Xue-Ru Fan; Avram J. Holmes; Hao-Ming Dong; Hai-Fang Li; Xi-Nian Zuo (Developmental Cognitive Neuroscience, 2023)
Pediatric neuroimaging datasets are rapidly increasing in scales. Despite strict protocols in data collection and preprocessing focused on improving data quality, the presence of head motion still impedes our understanding of neurodevelopmental mechanisms. Large head motion can lead to severe noise and artifacts in magnetic resonance imaging (MRI) studies, inflating correlations between adjacent brain areas and decreasing correlations between spatial distant territories, especially in children and adolescents. Here, by leveraging mock-scans of 123 Chinese children and adolescents, we demonstrated the presence of increased head motion in younger participants. Critically, a 5.5-minute training session in an MRI mock scanner was found to effectively suppress the head motion in the children and adolescents. Therefore, we suggest that mock scanner training should be part of the quality assurance routine prior to formal MRI data collection, particularly in large-scale population-level neuroimaging initiatives for pediatrics.